Post - Traumatic Pseudoaneurysm of The Superficial Temporal Artery: A Clinical Case and Review of Literature (British Journal of Multidisciplinary and Advanced Studies, 2025)
Post-traumatic pseudoaneurysm of the superficial temporal artery (STA) represents a rare clinical condition that usually follows blunt trauma; it manifests as pulsatile swelling along the course of the artery in the fronto-temporal site. In this paper, the Authors present a case of post - traumatic pseudoaneurysm of the right STA that developed 2 months after suffering a contusive trauma in the temporal site. With reference to the literature data, we also reviewed the pathophysiology involved in pseudoaneurysm formation and the approach to diagnose and management this type of injury. A thorough clinical examination with the various imaging modalities allows for a correct diagnosis. The treatment of choice is mostly vessel ligation and pseudoaneurysm excision.